The austere academy - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2000)
As their outrageous misfortune continues, the Baudelaire orphans are shipped off to a miserable boarding school, where they befriend the two Quagmire triplets and find that they have been followed by the dreaded Count Olaf.